Daya Hambat Ekstrak Kasar dan Fraksi Ekstrak Etanol Daun Gribong (Archidendron clypearia (Jack) I.C. Nielsen) Terhadap Bakteri Penyebab Jerawat - Insyira, Rania; Lingga, Rahmad; Salmi, Salmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Acne is a dysbiotic condition caused by Cutibacterium acnes and Staphylococcus epidermidis bacteria. Gribong (Archidendron clypearia (Jack) I.C. Nielson) has been empirically used as a treatment for facial problems by the people of Bangka Belitung. This study aims to test the potential of ethanol extract and fractions of gribong leaves against two bacteria that cause acne.Â This study is an experimental research conducted in four stages, namely phytochemical testing, antibacterial activity testing, minimum inhibitory concentration testing, and minimum bactericidal concentration testing and equivalence tests against clindamycin antibiotics as positive controls. The results of this study showed (1) Secondary metabolites contained in 96% ethanol extract, ethyl acetate fraction and n-butanol fraction are phenolics, flavonoids, tannins and saponins. Terpenoids were only found in the ethanol extract. The ethyl acetate fraction found no alkaloids and the n-hexane fraction contained only steroids. (2) The 96% ethanol extract, ethyl acetate fraction and n-butanol fraction had antibacterial activity. (3) The highest antibacterial activity was shown by the ethyl acetate fraction with KHM on C. acnes at 0.375% and on S. epidermidis at 1% and KBM for both bacteria at 2.5%. (4) The equivalence value of antibacterial activity of fractions to antibacterial antibiotic clindamycin is still relatively low but still has good antibacterial activity. In conclusion, the ethanol extract and its fractions have potential as anti-acne against C. acnes and S. epidermidis bacteria.